Larval morphology of Hygrobates foreli (Lebert, 1874), H. longiporus Thor, 1898 and H. trigonicus Koenike, 1895 (Acari, Hydrachnidia, Hygrobatidae) - Tuzovskij, Petr V. (Zootaxa, 2018)
This study presents a detailed taxonomic review of water mite larvae and females of three species of the genus Hygrobates Koch, 1837 found in the Fauna of Russia: Hygrobates foreli (Lebert, 1874), H. longiporus Thor, 1898 and H. trigonicus Koenike, 1895. The larvae described by Wainstein (1980) under the name H. longiporus and H. foreli were probably misidentified and belong to other species.